An analysis of an incident during the renovation work of a power boiler superheater. (November 2015) - Duda, Piotr; Felkowski, Łukasz; Dobrzański, Janusz
Highlights: The visual inspection, the material examination and the results from the numerical modeling are presented in order to explain the cause of an incident in a power boiler. Conducted analysis and testing formulated the hypothesis of failure. A block model of obtained failure algorithm is shown. Recommendations are presented in order to prevent accidents of this type in the future.